2022
DOI: 10.1002/jbio.202100271
|View full text |Cite
|
Sign up to set email alerts
|

Histological and biochemical effects of preventive and therapeutic vascular photobiomodulation on rat muscle injury

Abstract: The intravascular or transcutaneous application of photobiomodulation (PBM) over blood vessels (vascular photobiomodulation, VPBM) has been used for the treatment of inflammatory and chronic conditions with promising systemic results. This study evaluated the VPBM effects on a model of muscle regeneration after acute injury and compared the outcomes of preventive and therapeutic VPBM. Transcutaneous VPBM was administered over the rat's main tail vein. Serum levels of creatine kinase (CK), aspartate aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A recent published study showed in an acute muscle injury animal model that VPBM promoted a reduction in macroscopic injury size, reduction of inflammatory infiltration and myonecrosis after 5 days and an increase of immature muscle fibers. In addition, this study also showed a reduction in biochemical markers related to muscle injury even to the control group 25 . In context macrophages/monocytes are key cells in muscle repair coordination and macrophages/microglia are essential to the promotion of neuronal survival 14 …”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…A recent published study showed in an acute muscle injury animal model that VPBM promoted a reduction in macroscopic injury size, reduction of inflammatory infiltration and myonecrosis after 5 days and an increase of immature muscle fibers. In addition, this study also showed a reduction in biochemical markers related to muscle injury even to the control group 25 . In context macrophages/monocytes are key cells in muscle repair coordination and macrophages/microglia are essential to the promotion of neuronal survival 14 …”
Section: Discussionmentioning
confidence: 51%
“…In addition, this study also showed a reduction in biochemical markers related to muscle injury even to the control group. 25 In context macrophages/monocytes are key cells in muscle repair coordination and macrophages/microglia are essential to the promotion of neuronal survival. 14 Functional improvements described in the literature in experimental studies employing PBM administered locally after SCI are attributed to changes on the cellular and molecular levels, with a reduction in the inflammatory process through the modulation of mediators, such as IL1-β, a reduction in edema at the injury site and the functional restoration of damaged mitochondria, thereby avoiding cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations